2022
DOI: 10.3389/fmed.2022.907893
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations of chronic obstructive pulmonary disease in a cohort of Chinese never smokers goes along with decreased risks of recurrent acute exacerbation, emphysema and comorbidity of lung cancer as well as decreased levels of circulating eosinophils and basophils

Abstract: Acute exacerbations show a significant impact on disease morbidity and mortality in chronic obstructive pulmonary disease (COPD). In contrast to stable COPD, the association of smoking status with clinical and laboratory characteristics in patients with acute exacerbations of COPD (AECOPD) has not been well studied. In this retrospective study, we compared never smokers and ever smokers on their demographic, clinical, and laboratory characteristics in a Chinese clinical cohort of AECOPD. In this cohort compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Bacterial infections are commonly associated with AE-COPD [ 341 , 342 , 343 , 344 ] and COPD patients due to their compromised airways. Wang et al categorized AE-COPD patients as smokers or non-smokers and conducted an analysis of the hematological parameters, which demonstrated that smokers exhibited higher counts of eosinophils and basophils in BAL [ 345 ]. Moreover, Li and colleagues reported that, as compared to smokers, non-smokers with AE-COPD had higher FEV1/forced vital capacity (FVC) and experienced less wheezing and phlegm production [ 346 ].…”
Section: Cs-induced Lung and Other Diseasesmentioning
confidence: 99%
“…Bacterial infections are commonly associated with AE-COPD [ 341 , 342 , 343 , 344 ] and COPD patients due to their compromised airways. Wang et al categorized AE-COPD patients as smokers or non-smokers and conducted an analysis of the hematological parameters, which demonstrated that smokers exhibited higher counts of eosinophils and basophils in BAL [ 345 ]. Moreover, Li and colleagues reported that, as compared to smokers, non-smokers with AE-COPD had higher FEV1/forced vital capacity (FVC) and experienced less wheezing and phlegm production [ 346 ].…”
Section: Cs-induced Lung and Other Diseasesmentioning
confidence: 99%
“…COPD is one of the top five leading causes of mortality during the 21st century, especially within the oldest age group. For example, it was the third global cause of death in 2019, with approximately 3.23 million deaths [ 2 ]. In contrast, respiratory mortalities associated with BA are seven-fold lower than those reported for COPD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Characterized by bronchial hyper-reactivity and airway obstruction, this disease generally starts in childhood, although its adult onset is not uncommon [ 6 ]. COPD, by contrast, occurs primarily in middle-aged or older adults, with smoking being linked to nine out of ten cases [ 2 ]. This common and preventable chronic respiratory condition affects lung parenchyma and peripheral airways.…”
Section: Introductionmentioning
confidence: 99%
“…There is a high incidence of lung cancer 2 of 32 among people with COPD, and this association transcends the established connection that both conditions have with a smoking history. For instance, several studies have reported a heightened risk of lung cancer in people with COPD, independent of age or tobacco use [16][17][18][19][20][21][22][23]. The data suggest that COPD in those who smoke have a two to five-fold higher risk of developing lung cancer compared to non-smokers, with the overall survival rate in those with COPD and lung cancer significantly lower than those with lung cancer without COPD [17,24,25].…”
Section: Introductionmentioning
confidence: 99%